Awareness and Acceptability of Camarines Norte State College Vision and Mission, The Graduate School Goal and Objectives of Curricular Programs - Mabeza, Ma. Reina A.; Macasinag, Nora J.; Fajardo, Corazon S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study assessed the respondents’ extent of awareness and acceptability of the Camarines Norte State College (CNSC) vision and mission, the Graduate School goal and the objectives of curricular programs. A descriptive research survey was used in the study and employed a structured survey questionnaire in gathering the relevant data from the respondents. The findings revealed that the respondents which also identified as the stakeholders of the CNSC such as the students, parents, faculty members, employees, and alumni are highly aware on the CNSC’s vision and mission, the Graduate School goal and the objectives of its different curricular programs. Likewise, the findings revealed that the respondents highly accepted the CNSC mandates, the Graduates School goals and its different curricular objectives. Using One-way Analysis of Variance (ANOVA), results inferred that no significant differences on the extent of awareness of the respondents in terms of CNSC vision, mission, GS Goal and in the objectives of its different curricular programs. The study recommended that there may be an extensive dissemination of the CNSC vision, mission, the Graduate School goal and the objectives of its curricular programs during the beginning of the school term and these must be disseminated sustainably through different fora and to other platform of information like College Webpage, in local TV and radio programs, posted in bulletin boards, flyers and the like.